Derden verzet as a Legal Protection Effort for Third Parties In Realising Sustainable Development Goals (SDGs) - Siti Zulaichah; Yayuk Whindari; Sheila Kusuma Wardani Amnesti; Nurul Istiqomah (Magister Hukum Universitas Semarang, 2026)
This study aims to analyze the effectiveness of derden verzet as a legal protection mechanism for third parties in civil execution disputes in Indonesia and to assess its relevance to the achievement of Sustainable Development Goals (SDGs), particularly Goal 16 on peace, justice, and strong institutions. Employing normative legal research with a case approach, this article examines Decision No. 372/Pdt/2020/PT.Bdg and relevant procedural norms under the HIR/RBg framework, supported by doctrinal and human-rights-based justice literature. The findings show that derden verzet is conceptually designed to safeguard third-party property rights affected by final court judgments; however, its implementation remains constrained by procedural formalism, a heavy burden of proof, limited public awareness, and inadequate procedural safeguards in summons and evidentiary examination. In the analyzed case, the third party’s attempt to reclaim property rights was impeded despite indications that the transfer of rights occurred in the absence of good faith, demonstrating a gap between procedural compliance and substantive justice. This condition undermines legal certainty and weakens access to justice, contradicting the institutional objectives promoted by SDG Goal 16. The novelty of this study lies in repositioning derden verzet not merely as an extraordinary procedural remedy but as a substantive rights-protection instrument within a human-rights-oriented civil justice reform agenda, while identifying key normative deficiencies such as unclear standing requirements and undefined criteria of “harmed interests.” Accordingly, the study recommends clearer judicial guidelines and standardized procedural rules to strengthen third-party standing assessment, improve structured evidentiary review, and reduce excessive formalism to ensure more effective protection and a more accountable civil justice system.